(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This article will focus on the study and disposal of the oil content of Bukhara. Nestled in the heart of Central Asia lies the ancient city of Bukhara, rich in history, culture, and, notably, oil. The region’s oil reserves have been a source of fascination for centuries, drawing the attention of explorers, scientists, and entrepreneurs alike. The extraction, utilization, and disposal of Bukhara oil present a multifaceted study, blending elements of geology, chemistry, environmental science, and economics